Determination of the dependence of the plant growth characteristics on the concentration of petrochemiscals in the soil - Cherniak, Larysa; Mikhyeyev, Oleksandr; Madzhd, Svitlana; Lapan, Oksana; Dmytrukha, Tetyana; Petrusenko, Valentyna (My University, 2021)
The peculiarities of sanitary and hygienic rationing of the oil products content in environmental components were analyzed. It was established that the general ecological situation in our country and abroad is unsatisfactory and the issue of finding modern methods of standardizing the quality of environmental components, which would cover the indicators and criteria of their composition and properties, is becoming increasingly urgent. Together, it would ensure ecologically sustainable development of the biosphere in all hierarchical levels of its organization. It was established that such an assessment system does not exist today and therefore, there is no generally accepted universal method for assessing the quality of the environmental components. For this purpose, it is necessary to develop a methodology, in particular a method of biotesting, which will provide a generalized qualitative assessment of the ecological state of the environment, without being based on the quantitative characteristics of the MPC. The possibility of applying a new method of phytotesting of soil that was artificially contaminated with different types of petrochemicals in different concentrations per unit volume of soil using flax seedlings (Linum usitatissimum L.) was investigated. The growth characteristics of the test plants grown on artificially contaminated soil with petroleum products were presented. In the course of research, the possibility of studying the effect of petrochemicals on plants directly in artificially contaminated soil was confirmed. On the basis of the analysis of the obtained results, it was found that when the soil is contaminated with oil products, the aviation fuel has a greater impact on the shoots, whereas gasoline and diesel fuel have a lower impact on the roots in lower concentrations. At higher concentrations, their depressant effect is almost equal

Проаналізовано особливості санітарно-гігієнічного нормування вмісту нафтопродуктів у складових навколишнього середовища. Встановлено, що загальна екологічна ситуація в нашій країні та за кордоном є незадовільною і все більш актуальним стає питання пошуку сучасних методів стандартизації якості компонентів навколишнього середовища, які б охоплювали показники та критерії їх складу та властивостей. Разом це забезпечило б екологічно стійкий розвиток біосфери на всіх ієрархічних рівнях її організації. Встановлено, що на сьогодні такої системи оцінки не існує, а отже, загальноприйнятої універсальної методики оцінки якості компонентів довкілля. Для цього необхідно розробити методику, зокрема методику біотестування, яка забезпечить узагальнену якісну оцінку екологічного стану довкілля, не базуючись на кількісних характеристиках ГДК. Досліджено можливість застосування нового методу фітотестування ґрунту, штучно забрудненого різними видами нафтохімікатів у різних концентраціях на одиницю об’єму ґрунту, з використанням проростків льону (Linum usitatissimum L.). Наведено особливості росту дослідних рослин, вирощених на штучно забрудненому нафтопродуктами ґрунті. У ході досліджень була підтверджена можливість вивчення впливу нафтохімікатів на рослини безпосередньо в штучно забрудненому ґрунті. На підставі аналізу отриманих результатів встановлено, що при забрудненні ґрунту нафтопродуктами більший вплив на пагони має авіаційне паливо, а в менших концентраціях – бензин і дизельне паливо. . При більш високих концентраціях їх депресивна дія майже однакова
Keywords: bio tests; petroleum products; soil contamination; chemical pollution; біотести; нафтопродукти; забруднення грунтів; хімічне забруднення; кафедра екології та екоменеджменту